A SUSPECTED CASE OF ACUTE APPENDICITIS REVELAED TO BE ISOLATED SUBMUCOSAL LIPOMATOSIS OF APPENDIX ON COMPUTED TOMOGRAPHY: A CASE REPORT - PINTU BISWAS; MATAM SUPRIYA (International Journal of Medical Research and Review, 2024)
Symptomatic isolated submucosal intestinal lipomatosis is a rare entity [1,2]. Also, few cases have been reported in literature. Here, we are presenting computed tomography findings of a rare case of isolated submucosal lipomatosis of appendix presumptively diagnosed as acute appendicitis in a 72-year-oldfemale. This case highlights the importance of considering isolated submucosal lipomatosis as a differential diagnosis in instances of suspected acute appendicitis, especially when clinical findings are inconclusive.